Основы статистической теории моделирования технологических процессов - Пигнастый, Олег Михайлович (Київський національний університет технологій та дизайну, 2010)
Используя статистический подход, который широко распространен в естественных науках, построена модель производственно-технической системы. Состояние производственно-технической системы задается множеством предметов труда. Состояние предмета труда задано точкой в ​​фазовом технологическом пространстве. Введена функция распределения предметов труда по состоянию и записано кинетическое уравнение для функции распределения. Записана замкнутая систему динамических уравнений (уравнений баланса) для моментов функции распределения, где моменты функции распределения являются макро- параметрами

Using a statistical approach that is widespread in the natural sciences, a model of the production and technical system is built. The state of the production system is set by a multitude of objects of labour. The state of the subject of labour is given by a point in the phase of technological space. The distribution function of objects of labor by the state is introduced and the kinetic equation for the distribution function is written. A closed system of dynamic equations (balance equations) is written for the moments of the distribution function, where the moments of the distribution function are macro-parameters of the production and technical system.
Statistical Technological Process Modelling
Keywords: тип производства; PDE-модели поточных линий; незавершенное производство; производственная линия; PDE-модель производства; массовое производство; балансовые уравнения; production line; PDE-model of production; balance equations; production management system; stochastic process; work in progress; conveyor; subject of labour